Modeling and Simulation of Pretomanid Pharmacokinetics in Pulmonary Tuberculosis Patients - Lyons, Michael A. (Antimicrobial agents and chemotherapy, 2018)
Pretomanid is a nitroimidazole antibiotic in late-phase clinical testing as a component of several novel antituberculosis (anti-TB) regimens. A population pharmacokinetic model for pretomanid was constructed using a Bayesian analysis of data from two phase 2 studies, PA-824-CL-007 and PA-824-CL-010, conducted with adult (median age, 27 years) patients in Cape Town, South Africa, with newly diagnosed pulmonary TB. Combined, these studies included 63 males and 59 females administered once-daily oral pretomanid doses of 50, 100, 150, 200, 600, 1,000, or 1,200 mg for 14 days. The observed pretomanid plasma concentration-time profiles for all tested doses were described by a one-compartment model with first-order absorption and elimination and a sigmoidal bioavailability dependent on dose, time, and the predose fed state. Allometric scaling with body weight (normalized to 70 kg) was used for volume of distribution and clearance, with the scaling exponents equal to 1 and 3/4, respectively. The posterior population geometric means for the clearance and volume of distribution allometric constants were 4.8 ± 0.2 liters/h and 130 ± 5 liters, respectively, and the posterior population geometric mean for the half-maximum-effect dose for the reduction of bioavailability was 450 ± 50 mg. Interindividual variability, described by the percent coefficient of variation, was 32% ± 3% for clearance, 17% ± 4% for the volume of distribution, and 74% ± 9% for the half-maximum-effect dose. This model provides a dose-exposure relationship for pretomanid in adult TB patients with potential applications to dose selection in individuals and to further clinical testing of novel pretomanid-containing anti-TB regimens.